VD_FINDINFO HC / 2017 / 229 vom 27. Juli 2017 - VD Tribunal cantonal (2017)
RESPONSABILITÉ CONTRACTUELLE, FAUTE, FAUTE PROPRE, RUPTURE DU LIEN DE CAUSALITÉ | 101 al. 1 CO, 43 al. 1 CO, 44 al. 1 CO, 97 al. 1 CO